Constructing The State’s Financial Identity: A Critical Discourse Analysis Of The Indonesian Government’s Fiscal Narrative In Sri Mulyani Indrawati’s 2025 Budget Speech - Alim Akbar Nasir, Muhammad; Arifin, M. Bahri; Prafitri, Wilma (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study analyzes how the Indonesian government constructs its fiscal narrative and financial identity through Sri Mulyani Indrawati’s 2025 Budget Speech. Using Fairclough’s three-dimensional Critical Discourse Analysis, it examines linguistic features, production processes, and the socio-political context surrounding the speech. The qualitative analysis focuses on lexical choices, modality, rhetorical structuring, intertextual references, and the institutional setting of the national budgeting process. The findings show that the speech functions as more than a fiscal report; it strategically shapes public understanding of state finance. Technical economic terminology is interwoven with greetings, moral cues, and nationalist references to project authority, responsibility, and cultural legitimacy. Institutional framing and references to established economic doctrines further reinforce credibility. The speech ultimately serves two purposes: to legitimize fiscal decisions before lawmakers and to cultivate public trust by stressing stability, resilience, and collective responsibility. This demonstrates how budget speeches construct coherent narratives that support policy direction and state authority.